Measuring the Contribution of Social Policies to Regional Inequality Dynamic in Brazil - Raul Silveira Neto; Carlos Azzoni (European Regional Science Association (ERSA), 2011)
We decompose the recent changes in regional inequality in Brazil into its components, highlighting the role of spatially blind social programs. We aggregate personal income micro data to the state level, differentiating 9 income sources, and assess the role of these components in the observed changes in regional inequality indicators. The main results indicate that the largest part of the recent reduction in regional inequality in Brazil is related to the dynamics in the market-related labor income, with manufacturing and services favoring inequality reduction. Labor income in agriculture, retirement and pensions, and property rents and other sources favored concentration. The social programs Bolsa Família and Benefícios de Prestaç\~ao Continuada are responsible for more than 24% of the reduction in inequality, although they account for less than 1.7% of the disposable household income. Such positive impact on regional concentration is impressive, since the goals of the programs are clearly non-spatial.
Keywords: 330